ASSESSING THE TOURISM VALUE OF TEMAM WATERFALL: ENVIRONMENTAL AND ECONOMIC PERSPECTIVES - Agustina Sari, Evi; Rahma, Munaja; Purwanto, M. Bambang (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This study aims to assess the tourism value of Temam Waterfall in Lubuklinggau from an environmental and economic perspective. Temam Waterfall has excellent potential as a natural tourist attraction, but improper development can affect ecological sustainability and the sustainability of its financial benefits. This study uses a qualitative method with data collection techniques in the form of field observations, interviews with local stakeholders, and literature studies related to sustainable tourism. The study results show that Temam Waterfall has a solid natural attraction with the potential to attract domestic and foreign tourists. The findings show that the waterfall area is still relatively well maintained from an environmental perspective. However, some places must be handled to reduce the risk of ecosystem damage due to tourism activities. From an economic perspective, the potential of Temam Waterfall to increase local community income through tourism has begun to be seen, especially in the form of selling MSME products and providing tourism services. However, the sustainability of these economic benefits requires careful planning, especially in visitor management and infrastructure improvements. This study recommends the implementation of sustainable tourism by paying attention to environmental conservation and community empowerment. Collaboration between local governments, tourism managers, and the community is needed to develop Temam Waterfall as a leading destination without sacrificing its ecological aspects. Strengthening promotions and improving accessibility are also recommended to expand tourist attractions.